Особливості анодної поведінки срібла і його ювелірних сплавів у розчинах на основі роданіда калію - Дерібо, Світлана Германівна; Артеменко, Валентина Мефодіївна; Лещенко, Сергій Анатолійович; Корогодська, Алла Миколаївна (НТУ "ХПІ", 2017)
Досліджено анодну поведінку електродів зі срібла та ювелірного сплаву СрМ925 в розчинах роданіду калію. Встановлено області потенціалів, що відповідають активному розчиненню аноду та його переходу в активно-пасивний стан. Визначені кінетичні закономірності анодних процесів на сріблі та його сплаві, представлено механізм процесу електрохімічного полірування. Обґрунтовано оптимальні концентрації роданіду калію. Показано, що додавання до електроліту гліцерину сприяє підвищенню якості полірування при мінімальних втратах металу. Запропоновані режими проведення процесу.

Anodic behavior of electrodes from silver and silver alloy CрM925 in solutions of potassium rhodanide in a wide range of concentrations was investigated. It has been established that with increasing concentration of ligand (potassium rhodanide), both the peak values of the current density of active dissolution of silver and the current density in the region of the active-passive state of the anode increase as the peak increases. The method of polarization measurements determines the potential regions corresponding to the active dissolution of the anode and its transition to the active-passive state, where the electrolytic polishing process of silver and its alloy occurs exactly. The kinetic regularities of silver anode behavior in potassium rhodanide solution are determined and the nature of the slow stages during electrochemical polishing is revealed. The mechanism of the process of anodic polishing of silver, which includes adsorption on the surface of the anode of rhodanide ions (CNS¯), silver ionization, formation of the salt passive film AgCNS, its interaction with the solution with the subsequent joining of the ligand groups, the formation of soluble complex ions with different coordination numbers and the withdrawal is proposed. They are deep into the solution. The range of optimal concentrations of potassium rhodanide (4 – 5 mol/dm3) for the process of anodic dissolution of silver and an alloy in the electrochemical polishing mode was substantiated. It is shown that the addition to polyethylene (glycerol) of the electrolyte helps to improve the quality of polishing with minimal metal losses. The optimal composition of the solution was established and the regime for the electrochemical polishing of silver and the CрM925 alloy was proposed.
The specificities of anodic behavior of silver and its jewelry alloy in the potassium thiocyanate solution
Keywords: електрохімічне полірування; гліцерин; кінетичні закономірності; режими полірування; electrochemical polishing; silver; glycerol; kinetic patterns